El plan para la seguridad alimentaria, nutrición y erradicación del hambre 2025 de la CELAC y la Ley de Tierras y Territorios en Ecuador: análisis de convergencia - Calderón Guevara, Marco Napoleón (2017)
The world produces enough to feed the entire world population of 7 billion people. However, one in eight people on the planet goes to bed hungry every night. In Latin America and the Caribbean there are still 37 million people who are hungry and in Ecuador the reality is no different. Because of it, this research seeks to develop a qualitative-quantitative analysis of the Plan for the Eradication of Hunger 2025 of CELAC which at the level of recommendations proposes to its member countries and the Land and Territories Law, a policy for the democratization of the most important resource for food production: land. For that, an analysis of primary and secondary sources with statistical projections was carried out, interviewed an expert on issues related to agrarian reform and a field research where 50 producers explain their main problems to produce food. The conclusions and results define a difficult and precarious next food scenario, due to the smallholding of peasant properties. The Law of Lands and Territories does not change this reality in Ecuador; The CELAC Plan only recommends solutions that do not modify the exclusive and unequal structure in the field; Therefore, these two legal bodies have many binding points because they are "formal" statements that for the "real" application require political will and a real change of power relations in the agricultural area for the promotion of the rights of small producers.